Meta-analyses indicate that dietary probiotics significantly improve growth, immune response, and disease resistance in tilapia - Saba, Abdulwakil Olawale; Md Yasin, Ina Salwany; Azmai, Mohammad Noor Amal (Springer Nature, 2024)
Aquaculture is expanding globally, but intensive rearing conditions can cause diseases due to microbial infections leading to financial losses. Probiotics can be used in tilapia farming instead of antibiotics to improve fish health, growth and are environmentally friendly. We provide a synthesis (meta-analysis) of empirical findings to increase statistical power and produce strong evidence for well-informed decision-making with respect to the use of pro, pre, and synbiotics in tilapia culture. In this meta-analysis, we investigated the effects of dietary probiotics on the immune response modulation and resistance of tilapia against common diseases. A systematic search was performed, and the data from 67 studies were included for review and meta-analysis. Pre-challenge, dietary probiotics led to a significant increase (p < 0.001) in the weight gain and specific growth rate, a significant decrease (p < 0.001) in the feed conversion ratio, but a non-significant increase in survival (p > 0.05). However, probiotics significantly (p < 0.001) enhanced innate immunity based on serum lysozyme, phagocytotic activity, and phagocytotic index, while disease resistance (survival) of tilapia against pathogenic challenge was also significantly (p < 0.001) enhanced. From this study, three categories of probiotics were identified such as single-strain probiotics (SSP), multi-strain probiotics (MSP), and symbiotics (S). The use of synbiotics (probiotics + prebiotics) showed the best effect compared to other probiotic categories, however, more research is needed to ascertain the superiority of synbiotics over other categories. This study concluded that probiotics generally contribute significantly to the growth, immunity, and disease resistance of tilapia.